A child with tuberous sclerosis having Novel NRAS gene mutation - P. N. Liveinai; Neeraj Kumar; Jyoti Kadian; Dinkar Yadav; Kapil Bhalla (Journal of Family Medicine and Primary Care)
Tuberous sclerosis (TS) is a rare genetic disorder of autosomal-dominant inheritance. Mutations on either of the two genes Tuberous Sclerosis Complex 1 (TSC1) or Tuberous Sclerosis Complex 2 (TSC2) will lead to hamartomas formation involving many organs, such as the brain, heart, kidneys, skin, lungs, and liver. This case report is about an 11-month-old boy with epilepsy and hypomelanotic macules. MRI of the brain showed cortical tubers and subependymal nodule which confirms the diagnosis of Tuberous Sclerosis. Genetic analysis by Whole Exome Sequencing showed a novel genetic mutation in NRAS gene suggestive of Noonan syndrome-6.